Traditional vs Online Games: Their Benefits for Young Learners - Suwastini, Ni Komang Arie; Radhaswati, I Dewa Ayu Agung; Jayantini, I Gusti Agung Sri Rwa; Artini, Ni Nyoman (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2023)
AbstractAs young learners like to learn in a fun atmosphere with engaging interactions, the present study argues that when children learn English as a foreign language, implementing games in teaching English can benefit young learners. The research was conducted following the library research method, where the content of the research from previous studies on English for young learners and the benefits of using games in teaching English for young learners were collected with the keywords